The Fly Homologue of MFSD11 Is Possibly Linked to Nutrient Homeostasis and Has a Potential Role in Locomotion: A First Characterization of the Atypical Solute Carrier CG18549 in Drosophila Melanogaster - Mikaela M. Ceder (MDPI AG, 2021)
Cellular transport and function are dependent on substrate influx and efflux of various compounds. In humans, the largest superfamily of transporters is the SoLute Carriers (SLCs). Many transporters are orphans and little to nothing is known about their expression and/or function, yet they have been assigned to a cluster called atypical SLCs. One of these atypical SLCs is MFSD11. Here we present a first in-depth characterization of the MFSD11, CG18549. By gene expression and behavior analysis on ubiquitous and brain-specific knockdown flies. CG18549 knockdown flies were found to have altered adipokinetic hormone and adipokinteic hormone receptor expression as well as reduced vesicular monoamine transporter expression; to exhibit an altered locomotor behavior, and to have an altered reaction to stress stimuli. Furthermore, the gene expression of CG18549 in the brain was visualized and abundant expression in both the larvae and adult brain was observed, a result that is coherent with the FlyAtlas Anatomy microarray. The exact mechanism behind the observed behaviors is not fully understood, but this study provides new insights into the expression and function of CG18549. Clearly, these results provide a strong example as to why it is vital to fully characterize orphan transporters and through that gain knowledge about the body during normal condition and disease.